Particulate macronutrient exports from tropical African montane catchments point to the impoverishment of agricultural soils - Stenfert Kroese, J.; Quinton, J.N.; Jacobs, S.R.; Breuer, Lutz; Rufino, Mariana C. (Copernicus GmbH, 2021)
Agricultural catchments in the tropics often generate high concentrations of suspended sediments following the conversion of natural ecosystems. The eroded fine particles are generally enriched with carbon (TC) and nutrients (TN and TP) originating from the topsoil of agricultural land. Sediment-associated TC, TN and TP are an important loss to the terrestrial ecosystem and tightly connected to an increase in riverine particulate TC and nutrient export. Soil nutrient depletion can limit crop growth and yields, whereas an excess of nutrients in streams can cause eutrophication in freshwater systems. Streams in East Africa, with widespread land conversion from forests to agriculture, are expected to receive high loads of sediment-associated TC, TN and TP. In this study, we assess the effect of land use on particulate TC, TN and TP concentrations. Suspended sediments (time-integrated, manual-event-based and automatic-event-based sediment samples) were analysed for TC, TN and TP concentrations collected at the outlet of a natural montane forest (35.9), a tea-tree plantation (33.3) and a smallholder agriculture (27.2 km2) catchment in western Kenya during a wet sampling period in 2018 and a drier sampling period in 2019. Particulate TC, TN and TP concentrations were up to 3-fold higher (p<0.05) in the natural forest catchment compared to fertilized agricultural catchments. However, because of higher sediment loads from the smallholder agriculture catchment, the total sediment-associated loads of TC, TN and TP were higher compared to the natural forest and tea-tree plantation catchment. The higher C:N ratios in the natural forest suggest that the particulate nutrients are of organic origin due to tighter nutrient cycles, whereas lower ratios in both agricultural catchments suggest a mixture of mineral and organic sediment sources. The findings of this study imply that with the loss of natural forest, the inherent soil fertility is progressively lost under the current low fertilization rates and soil management strategies.